National qualifications frameworks developments in Europe 2019 : Qualifications frameworks: transparency and added value for end users - (:unkn) unknown (Publications Office of the European Union, 2020)
"This booklet comes at a time when Europe is devising its plans for recovery from the economic and social crisis induced by the Covid-19 pandemic. The subsequent faster shift to the digital and green economy, and the need for many people to find new jobs in different sectors, will require large-scale upskilling and reskilling initiatives. Recent experience in working and learning remotely may encourage more citizens to look for opportunities beyond regional or national borders. With the widely accepted European and national qualifications frameworks for lifelong learning (EQF and NQFs), we have powerful tools that make it easier for people to 'carry their skills and credentials' with them to different contexts. [...] This booklet on the latest national qualifications frameworks developments, aims to summarise and illustrate the state of play of the 43 frameworks created to date in the EU, EFTA, candidate and potential countries and the UK." (editor; BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Europa